2013
DOI: 10.4236/fns.2013.48a024
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enrichment and Antimicrobial Protection of Fresh-Cut Mango Applying Bioactive Extracts from Their Seeds By-Products

Abstract: The effect of the application of ethanolic extract of “Haden” mango seeds to increase the antioxidant and antimicrobial capacity of fresh-cut mango flesh was evaluated. Phenolic HPLC analysis revealed that gallic acid was the major identified compound in the ethanolic extract (586.68 mg/g). Fresh-cut mango was treated for immersion within the ethanolic extract, packed and stored at 5 during 15 days. The content of phenolic compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The increment of antioxidant activity observed in treated products can be justified easily as the simple addition of antioxidants compounds present in EOs. Similar results were observed in other studies; mango seed extract was added to fresh‐cut mango “Haden” resulting in an increase in TPC (7.4‐fold), flavonoids (3.1‐fold) and antioxidant capacity by DPPH, TEAC, and ORAC (2.3–2.8‐fold) when compared to control fruits (Vega‐Vega et al, ). Also, orange seed extract was added to orange wedges obtaining similar results (Cruz‐Valenzuela, Carrazco‐Lugo, Vega‐Vega, Gonzalez‐Aguilar, & Ayala‐Zavala, ).…”
Section: Resultssupporting
confidence: 89%
“…The increment of antioxidant activity observed in treated products can be justified easily as the simple addition of antioxidants compounds present in EOs. Similar results were observed in other studies; mango seed extract was added to fresh‐cut mango “Haden” resulting in an increase in TPC (7.4‐fold), flavonoids (3.1‐fold) and antioxidant capacity by DPPH, TEAC, and ORAC (2.3–2.8‐fold) when compared to control fruits (Vega‐Vega et al, ). Also, orange seed extract was added to orange wedges obtaining similar results (Cruz‐Valenzuela, Carrazco‐Lugo, Vega‐Vega, Gonzalez‐Aguilar, & Ayala‐Zavala, ).…”
Section: Resultssupporting
confidence: 89%
“…In accordance with our results, Vega-Vega et al 42 reported the effectiveness of mango seed extract (gallic acid 59%) as an antimicrobial agent applied on fresh-cut mango. This treatment showed 1.5 and 0.72 log unit reductions in yeasts/molds and mesophilic aerobes respectively after 15 days of refrigerated storage (5 ∘ C).…”
Section: Discussionsupporting
confidence: 93%
“…Mango seeds were chopped in small pieces (10 g) and put in a flask with 100 mL of ethanol: water (7:3). The sample was left to macerate in darkness for 10 days at 25 °C [ 8 ]. Subsequently, the extract was filtered through a Whatman No.1 (Springfield Mill, Maidstone Kent, UK).…”
Section: Methodsmentioning
confidence: 99%
“…These compounds are able to neutralize free radicals and inactivate microbial cells. Due to such properties, extracts from mango seeds and other byproducts could be added to several food matrices such as milk, cereal products and fresh-cut mango, with good results in terms of functionality and antimicrobial protection [ 6 , 7 , 8 ]; however, the sensory aspect has not especially been taken into account and mango seed constituents could have different effects on the sensory quality of foods.…”
Section: Introductionmentioning
confidence: 99%